Characterization of chemical and physical changes in atmospheric aerosols during fog processing at Baengnyeong Island, South Korea. (1st June 2022) - Park, Taehyun; Jung, Dong Hee; Lim, Yongjae; Ban, Jihee; Kim, Kyunghoon; Kang, Seokwon; Park, Gyutae; Choi, Siyoung; Kim, Hyunjae; Sung, Minyoung; Choi, Yongjoo; Boris, Alexandra J.; et al.
Abstract: In situ interactions between aerosols and atmospheric fog droplets were explored using aerosol physical and chemical measurements and fog samples taken at the Baengnyeong Island Intensive Air Quality Monitoring Station, South Korea during June 16th to July 21st, 2014. To investigate wet scavenging by fog, aerosols were characterized by aerosol mass spectrometer before, during, and after five fog events. Total non-refractory PM1 mass decreased by an average of 22.8% with the onset of fog. The scavenging efficiency ( η ) of organics was 7–34%, where lower η was associated with lower organic oxidation and hygroscopicity. The η was 16–68% for NH4 +, -1–35% for SO4, and 17–86% for NO3 −, consistent with previous studies and the relatively high NO3 − hygroscopicity. The variation in scavenging was size dependent for both organics and NO3 − . Particles with lower NO3 − η on 7/18 were smaller (mode = 346 nm), while those with higher NO3 − η were larger (593 nm). Differences in mass were also explored before and after fog events. Three episodes showed overall decreases in all the components after the fog event, while two episodes showed overall increases, most notably in organics. Both organic mass and SO2 + /H2 SO4 + ratio were used to indicate the prevalence of hydroxymethanesulfonate (HMS), an aqueous secondary organic aerosol (aqSOA) formation marker, which increased after the 7/18 fog episode. The aerosol carbon oxidation state decreased toward the end of all fog episodes suggesting possible molecular fragmentation and loss of highly oxidized functional groups. On 7/18, the organic content developed lower O:C and higher H:C moving "up" a slope of −1 in a van Krevelen diagram over the course of the fog episode, indicating carboxylic acid or hydroxycarbonyl loss. This study explores relatively rare time-resolved aerosol fog processing measurements. The results confirm previously established relationships between scavenging and particle size, demonstrate overall increases and decreases in particle mass after fog processing based on dominant local chemistry and wet deposition, and show predominant decreases in organic oxidation after fog processing, thereby, contributing to our understanding of particle processing and organic cycling in the atmosphere. Highlights: Particle composition and size measurements were used to explore fog processing. Organic scavenging efficiency η (7–34%) was lower in less-oxidized particles. Mass decreased after 3 fog events and increased, notably in organics, in 2 events. The aerosol carbon oxidation state decreased by the end all fog episodes.